2005
DOI: 10.1002/nau.20190
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence and voiding dysfunction after radical retropubic prostatectomy (prospective urodynamic study)

Abstract: These data suggest that the main cause of incontinence after RRP is sphincteric weakness. In the continent group, those who became immediately continent had significantly higher maximum urethral closure pressure values at rest and at voluntary sphincteric contraction even before the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 30 publications
3
112
1
4
Order By: Relevance
“…Previous studies have already proved that the functional urethral length is decreased after RRP, and that its postoperative values are significantly different in continent and incontinent patients [5,6] . It has also been proved that preoperative sphincter pressure parameters might partly influence postoperative continence.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have already proved that the functional urethral length is decreased after RRP, and that its postoperative values are significantly different in continent and incontinent patients [5,6] . It has also been proved that preoperative sphincter pressure parameters might partly influence postoperative continence.…”
Section: Discussionmentioning
confidence: 95%
“…Recent publications based on surveys with high case numbers estimate its frequency at between 6 and 20% [1][2][3][4] . Some studies dealing with postprostatectomy incontinence focused on urodynamic factors being responsible for incontinence [5][6][7][8] , whereas others tried to analyze the impact of the pre-and perioperative factors ( table 1 ) on urinary incontinence [2][3][4][9][10][11][12][13][14][15][16][17] . Some of the authors showed no association between the above-mentioned factors and postoperative incontinence [2, 11-13, 15, 17] , while others believed that older age, lack of a nerve-sparing technique, presence of anastomotic stricture, bladder neck resection and creating vesicourethral anastomosis without a long, partially intraprostatic portion of the urethra could be responsible for incontinence or at least represent risk factors delaying continence [1,3,4,9,10,14,16,[18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…7,19,22 There were statistically significant decreases of maximum urethral closing pressure, functional profile length, and bladder compliance in the incontinent group as compared with the continent group in both laparoscopic and open surgery. As some studies reported that urethral closure pressure and functional urethral length are indeed the dominant factors that determine continence in the residual sphincter, the degradation of the urethral sphincteric function expressed as a decrease of urethral closing pressure and functional profile length is suggested to be a major factor contributing to the postoperative occurrence of urinary incontinence.…”
Section: Discussionmentioning
confidence: 95%
“…These results were predictors of stress UI after prostatectomy, suggesting that for incontinent patients, immediate intervention is more appropriate than watchful waiting. Majoros et al [15] have demonstrated that those patients who were immediately continent following the removal of the bladder catheter had had a higher preoperative MCUP. Along the same line, Dubbelman et al [16] found the UPP to be a good preoperative predictor of UI when instructing patients about pelvic floor muscle exercises.…”
Section: Discussionmentioning
confidence: 99%